STUDY KESIAPAN CALON GURU SD DALAM MENERAPKAN HOTS - Rizki Ananda; Diana Fatika Sari; Nonik Nugraheni; Seri Selfiani; Ummi Rosydah Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the readiness of prospective elementary school teachers in implementing Higher Order Thinking Skills (HOTS) in the learning process. The research was conducted based on the importance of HOTS-oriented learning in improving students’ critical, creative, and problem-solving abilities in the 21st century. The purpose of this study was to determine the level of readiness of prospective elementary school teachers in understanding, planning, and applying HOTS-based learning. This research employed a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The participants of this study were prospective elementary school teachers involved in teaching practice activities. The results showed that most prospective teachers had a good understanding of the HOTS concept; however, several obstacles were still found in its implementation, particularly in designing learning activities and assessment instruments based on HOTS. In addition, limited teaching experience and lack of training were factors influencing their readiness. Therefore, support through training and continuous guidance is needed to improve the competence of prospective teachers in implementing HOTS effectively in elementary school learning. Keywords: readiness of prospective teachers, HOTS, Elementary School.